Indirect methods of dried sewage sludge contamination assessments. Issue 9 (28th July 2016) - Werle, Sebastian; Dudziak, Mariusz; Grübel, Klaudiusz
ABSTRACT: Thermal conversion (combustion, co-combustion, gasification and pyrolysis) appears to be the most promising alternative for sewage sludge management in the future. Nevertheless, safe and ecological usage of sewage sludge as a fuel requires information about their contamination. The aim of this paper is to present the photoacoustic spectroscopy (PAS) as a good method for contamination assessments of dried sewage sludge. Two types of granular sewage sludge: Sewage sludge 1 (SS1) taken from Polish wastewater treatment plant operating in the mechanical-biological system and sewage sludge 2 (SS2) taken from mechanical-biological-chemical wastewater treatment plant with phosphorus precipitation were analysed. The spectrophotometer FTIR Nicolet 6700 equipped with photoacoustic cell (Model 300, MTEC, USA) was used. The comparison with the most popular analytical methods (GC-MS) was also done. The results of PAS studies confirm the difference between the SS1 and SS2 which is in agreement with the GC-MS analysis. Higher absorbance was observed at each wavelength characteristics for the oscillator of chemical moieties for the SS1 with respect to the SS2.